High Dose-Rate Brachytherapy in Recurrent High-Risk Head and Neck Cancer - Rudrappa Palled, Siddanna; Loni, Rahul; Pasha, Tanvir; Bondel, Shwetha; Chavan, Purushottam; Shenoy, Ashok; Naveen, Thimmaiah; Lokesh, V (Reports of Radiotherapy and Oncology, 2019)
Background: Thirty to fifty percent of HNSCC patients treated with chemoradiation therapy present with recurrence and can be treated with maximum debulking surgery combined with re-irradiation. Re-irradiation can be done using external beam radiation therapy (EBRT) or brachytherapy. The advantage of brachytherapy over EBRT is that owing to rapid dose falls off, a higher dose can be delivered to the target area sparing normal tissue. Hence, we evaluated toxicity and outcomes [overall survival (OS) and disease-free survival (DFS)] in high-risk (HR) recurrent HNSCC patients undergoing re-irradiation using interstitial brachytherapy following surgery. Objectives: To evaluate toxicity and outcomes of re-irradiation using Interstitial High Dose-Rate Brachytherapy (HDR-BRT) in high-risk Head and Neck Squamous Cell Carcinoma (HNSCC) patients. Methods: Ten biopsy-proven recurrent HNSCC patients treated with primary chemoradiation therapy who had the HR of the second recurrence at nodal disease were evaluated. All patients underwent surgery followed by the intraoperative placement of catheters in a single plane, at 10 - 12 mm apart and fixed with stay sutures. The CT simulation was done on the 5th - 7th postoperative day. Volumetric optimization was done with a 5-mm dwell position. The dose of 30 Gy/10 Fractions, 3 Gy/Fraction, two fractions per day, 6 hours apart after 5 days was planned. Results: The DFS and OS for the entire cohort in 1 and 2 years were 60% and 40%, respectively. One patient had carotid blowout where the disease was stuck to the carotid vessel. No other significant acute or late toxicity was noted. Conclusions: The HDR-interstitial brachytherapy in the recurrent HR, HNSCC with the intraoperative placement of catheters at tumor bed provides reasonably good local control without significant acute or late toxicity.